A QUESTIONNAIRE EVALUATION OF QMC COLD DRY CLOTHING BY MEN STATIONED IN THE ANTARCTIC. - Rosinger,George; McGinnis,John M. (1959)
The report is based on questionnaire which was designed to secure information concerning the performance of Quartermaster Corps cold weather clothing under Antarctic conditions. Copies of the questionnaire were completed during the 1957-1958 International Geophysical Year by 30 men who were stationed in the Antarctic. In addition to answering the questions asked, many of the men made additional comments concerning the clothing and its functioning at low temperatures. Since the conditions experienced (i.e., temperature, wind-speed, hours of continuous exposure, clothing worn, type of activity, etc.,) varied considerably from respondent, to respondent, the data are not readily quantifiable. However, where appropriate some frequencies, means, and medians have been presented. (Author)